The utility of balloon enteroscopy in the diagnosis of histiocytic sarcoma of the small intestine: A case report. (21st February 2013) - Miyazaki, Tamihiro; Arihiro, Seiji; Mitobe, Jimi; Aoki, Yoshihiko; Takikawa, Shingo; Saruta, Masayuki; Matsuoka, Mika; Koike, Kazuhiko; Kato, Tomohiro; Kashiwagi, Hideyuki; Ikegami, Masahiro; Tajiri, Hisao
Abstract : The diagnosis of the rare neoplasm histiocytic sarcoma (HS) relies on morphology and the presence of immunophenotypic features of histiocytic lineage. More than 57 cases, including 16 cases involving the gastrointestinal (GI) tract, have been described since the World Health Organization issued its classification system for tumors of hematopoietic and lymphoid tissue in 2001. HS is often diagnosed in its late stages, at which point the prognosis is poor. Only a small proportion of these patients can undergo surgical resection with curative intent. The present report describes how HS can be diagnosed at a stage of favorable prognosis using balloon enteroscopy (BE), thereby enabling surgical resection before the development of metastases. This strategy is reviewed in the setting of a patient with jejunal HS, followed by a discussion of data from 16 other reported cases of GI HS.